What's behind the rise in profitability in the US in the 1980s and 1990s? - Wolff, Edward N. (2003)
Profitability in the US has been rising since the early 1980s and by 1997 was at its highest level since its post-World War II peak in the mid-1960s, and the profit share, by one definition, at its highest point. In this paper, I examine the role of the change in the profit share and capital intensity, as well as structural change, on movements in the rate of profit between 1947 and 1997. Its recent recovery is traced to a rise in the profit share in national income, a slowdown in capital-labour growth at the industry level, and employment shifts to relatively labour-intensive industries. Reproduced.
Keywords: Profits - United States; Profits